2021
DOI: 10.3390/jpm11111155
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Promote a Healthy Sexuality among School Adolescents: A Scoping Review

Abstract: Schools are particularly suitable contexts for the implementation of interventions focused on adolescent sexual behavior. Sexual education and promotion have a multidisciplinary nature. Nurses’ role and the spectrum of the carried-out interventions is not clear. We aimed to identify interventions that promote a healthy sexuality among school adolescents. Our review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews and was registered in the Open Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…One scoping review to promote healthy sexuality, which includes sexual agency, is unable to provide a definitive recommendation on what intervention is best implemented to promote healthy sexuality due to different contexts and poor trial design. However, the said review has highlighted the importance of programs and interventions that are multi-faceted and affect not only knowledge and cognition, but also a person’s social and emotional dimensions as well as their well-being [ 45 ]. The recent passage of the Philippine Reproductive Health Law, which has specific provisions for adolescent and youth reproductive health guidance and counseling, reproductive health education for adolescents, and prevention and management of reproductive health guidance and counselling, is a step in the right direction [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One scoping review to promote healthy sexuality, which includes sexual agency, is unable to provide a definitive recommendation on what intervention is best implemented to promote healthy sexuality due to different contexts and poor trial design. However, the said review has highlighted the importance of programs and interventions that are multi-faceted and affect not only knowledge and cognition, but also a person’s social and emotional dimensions as well as their well-being [ 45 ]. The recent passage of the Philippine Reproductive Health Law, which has specific provisions for adolescent and youth reproductive health guidance and counseling, reproductive health education for adolescents, and prevention and management of reproductive health guidance and counselling, is a step in the right direction [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the risk approach does not cover the positive sexual health content that adolescents themselves wish to learn more about ( 17 , 25 , 31 ), which is perhaps why another review study found evidence of positive intervention effects when adolescents participate in the planning and implementation of programs ( 8 ). The health promotion approach shows promising evidence of effect ( 2 , 5 , 32 ), nonetheless, the health promotion perspective regarding adolescent sexual health is still understudied ( 5 , 14 , 23 ). There is a lack of synthesized evidence on the sexual health resources that adolescents want to learn about that can promote sexual health and well-being, e.g., sexual health literacy ( 14 ), self-esteem ( 6 ), respect and social skills regarding sexuality ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous review studies covering adolescent sexual health have primarily focused on North America ( 33 ) or employed a global perspective ( 32 , 34 ). Europe differs in many ways from North America, for instance, politically, culturally, and socio-economically which affects education as well as sexual health approaches in schools ( 35 , 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of services, evidence shows that school health programs can support young people in adopting lifelong behaviours and attitudes that reduce their risk of HIV, other STIs, and pregnancies [ 14 ], [ 15 ],[ 16 ]. Based on this, the South African government has subsequently taken steps to put an Integrated School Health Program (ISHP) in place [ 8 ] but evidence of successes and challenges are not currently available as these projects often have limited coverage or limited periods of implementation or follow-up [ 9 ].…”
Section: Introductionmentioning
confidence: 99%